Beyond totalitarianism: Stalinism and Nazism compared - Geyer, Michael (Cambridge University, 2013)
In essays written jointly by specialists on Soviet and German history, the contributors to this book rethink and rework the nature of Stalinism and Nazism and establish a new methodology for viewing their histories that goes well beyond the now-outdated twentieth-century models of totalitarianism, ideology, and personality. Doing the labor of comparison gives us the means to ascertain the historicity of the two extraordinary regimes and the wreckage they have left.